Factors influencing consumer willingness to pay for rabbit meat in the Daveyton and Etwatwa areas of Gauteng province, South Africa - Noinoi, Lekgau Jenifer; Leonah, Mthombeni Danisile; Akwasi, Antwi Michael (Asian Development Policy Review, 2024)
The purpose of the study was to determine the price point at which customers in the study locations are willing to pay for rabbit meat. The data was gathered by administering a semi-structured questionnaire through face-to-face interviews with a randomly selected sample of 382 respondents. The acquired data was analyzed using the Statistical Package for Social Science (SPSS), specifically version 28.0. The researchers utilized the contingent valuation approach to ascertain the consumers’ willingness to pay (WTP). The results showed that 83% of the respondents were prepared to pay for rabbit meat if their local meat outlet introduced it. About 43.7% of the respondents rejected the initial bid of R45/kg but accepted the discounted bids; 21% of the respondents accepted both the initial and discounted bids; 16.5% of the respondents only accepted the initial bid; and 18.6% of the respondents rejected both the initial and discounted bids. Furthermore, the results revealed that as monthly income increases, so does the respondents’ willingness to pay for rabbit meat. Although respondents showed interest in the purchasing and consumption of rabbit meat, they were not willing to buy the meat at a price of more than R40/kg. This indicates that when the seller introduces the meat to the local meat market in the study areas, they should be price-conscious.